No stake in victory : North African soldiers of the Great War - Rogan, E (Wiley, 2014)
The men of North Africa had no stake in the European war that erupted in August 1914. Over three hundred thousand Berber and Arab men from Algeria, Morocco, and Tunisia fought in Belgium and France. Many were wounded in some of the bloodiest engagements on the Western Front. Thousands were taken prisoner. As many as forty-five thousand never returned home, dying for a colonial power that had reduced them to second-class citizens in their own homelands. One particular aspect this article will focus on addresses the Muslim soldiers taken prisoner by the Germans who were interned in a special camp where they were recruited to the Ottoman army. Thousands joined the Ottoman Jihad effort that German war planners hoped might provoke uprisings among colonial Muslims in the British, French, and Russian Empires to undermine the Entente war effort. Redeployed in Mesopotamia and the Hijaz, these North African soldiers were as ill-served by the Ottoman Empire as they had been by the French. North African survivors of World War I resumed their lives as colonial subjects in their home countries under the intensified imperial rule of the interwar years.